Kesulitan Menyimak dalam Pembelajaran Bahasa Indonesia (Penelitian Studi Kasus Pada Siswa Kelas 3 Sekolah Dasar Inklusi X Bandung) - Rai Bagus (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2017)
The difficulty of listening become entry barriers to student information. Barriers could be any perception or wholeness of the information is up to the student. The purpose of this research is to find a case of learning to listen appears to be an aberration, then the deviation is analyzed based on the stage to look at the factors behind these deviations, while the final stage of this case study is to provide a response in the form of treatment in a particular context or in commonly called the case study evaluation phase. This study used a qualitative descriptive naturalistic research method to obtain data in a systematic, factual, and accurate. The data in this study are oral and written data. Oral data obtained using data collection techniques such as interviews and observations of the student, while data obtained using a form of writing instruments in the form of tests. The results showed that (1) the difficulty listening to experienced students (X) is caused by a disturbance in the sense of hearing; (2) auditory disorders occur because the student (X) had an accident in public pools; (3) the motivation of the teacher role for the case experienced by the student (X); (4) student (X) requires a special service in the learning process listening skill.